CONTENT AND FEATURES OF THE ADMINISTRATIVE AND LEGAL STATUS OF THE MILITARY LAW ORDER SERVICE IN THE ARMED FORCES OF UKRAINE (Bulletin of criminological association of Ukraine, 2024)
It is emphasized that the administrative-legal status is a complex concept that incorporates the elements that are determined by the norms of administrative law. It is based, first of all, on the rights and obligations of the subject, which in the context of a government body are revealed in its powers. The scope of the latter directly depends on the purpose and objectives of the existence of this body, which in turn determine the functions and responsibilities. It is concluded that the Law Enforcement Service of the Armed Forces of Ukraine is a departmental law enforcement body. Its administrative-legal status is a complex legal phenomenon, the content of which is a set of interrelated elements that reveal the essence of the Law Enforcement Service's activities, its significance and the role that it performs in the ranks of the Armed Forces of Ukraine, as well as in relations with other subjects. It is argued that the elements of this status are: the purpose of creation - the implementation of law enforcement activities; the purpose, which outlines the main directions for implementing this goal; general and additional tasks, the functions determined by them, as well as the rights and responsibilities of its servicemen. It has been established that the features of the administrative and legal status of the Military Law and Order Service in the Armed Forces of Ukraine include: an exclusive legislatively defined list of tasks that cannot be expanded by subordinate regulatory legal acts; the departmental nature of its competence, its application exclusively to those relations that arise in the sphere of activity of the Armed Forces of Ukraine, its servicemen and employees; limited powers in terms of the lack of the ability to independently carry out operational and search activities and investigative actions.
Keywords: administrative and legal status; rights; duties; tasks; functions; Military Law and Order Service